Related factor of Knowledge by Stroke in Institute of Higher Education Employees - Novida Rizky Wardhani; Santi Martini (Jurnal Berkala Epidemiologi, 2014)
Stroke is a non-communicable disease that causes death in the top ranks in urban areas which around 28.5% in Indonesia at 2011. Strokes begin at the productive age. This study aims to determine factors associated with knowledge about stroke in workers of educational institutions in Surabaya. This type of research is an observation analytic study using a cross-sectional study design. The questionnaire was given to 142 respondents. Dependent variables in this study were knowledge of stroke risk factors, level of initial stroke recognition, and how to handle it. The independent variables are age, sex, and level of education. Data analysis using chi-square test and spearman test. The results showed a level of knowledge of stroke risk factors 78.9% of respondents in the level of "good" knowledge about stroke risk factors, the level of recognition of early symptoms of the Face, Arm, Speech, and Time (FAST) method of respondents mostly in the category of "not good", and 63.4% of respondents had knowing how to handle it properly. The analysis showed that there was a significant relationship between sex with the level of knowledge of stroke risk factors (p = 0.020) and between the level of education with the level of recognition of early symptoms of stroke (p = 0.006; r = 0.229). The conclusion of this study is that respondents in the level of knowledge in both categories regarding stroke risk factors, how to do the treatment is correct, the health service chosen is also correct that is the hospital, the duration of treatment is less than 3 hours and only the level of recognition of early symptoms of stroke still not well known.